Model Aplikasi Perpustakaan Berbasis Web dengan Fitur Booking pada Sekolah Menengah Kejuruan - Nurfajriyah, Witri Sari; Bahar, Bahar (STMIK Banjarbaru, 2024)
The process of collecting book data and recording borrowing transactions is still done manually, causing the library management system at the Amuntai 1 State Vocational High School to be ineffective. This research aims to develop a Web-based application system model to assist library administration management. The system development method adopts four main phases in the Waterfall method (system analysis, system design, system construction, and system testing). The Web-based application system was developed using the PHP programming language and MySQL database. The framework used on the back-end is Laravel and on the front-end is Tailwind CSS. System testing was carried out to validate the main functional features, in the form of: loan, return, and fine features, as well as the online booking feature before lending transactions, which is new in this research. Blackbox testing results in the final testing phase (iteration 3) show that the overall application functionality has been effective in fulfilling its functional objectives, with suggestions for improvements to improve user experience and system efficiency.Keywords: Information Systems; Library; Web Based; Online booking; Blackbox Testing AbstrakProses pendataan buku serta pencatatan transaksi peminjaman yang masih dilakukan secara manual menyebabkan sistem pengelolaan perpustakaan pada Sekolah Menengah Kejuruan Negeri 1 Amuntai tidak efektif. Penelitian ini bertujuan mengembangkan model sistem aplikasi berbasis Web untuk membantu manajemen pengelolaan administrasi perpustakaan. Metode pengebangan sistem mengadopsi empat fase utama dalam metode Waterfall (Analisis sistem, desain sistem, konstruksi sistem, dan pengujian sistem). Sistem aplikasi berbasis Web dikembangkan menggunakan bahasa pemrograman PHP dan database MySQL. Framework yang digunakan pada back-end adalah Laravel dan pada front-end adalah Tailwind CSS. Pengujian sistem dilakukan untuk memvalidasi fitur-fitur fungsionalitas utama, berupa fitur: peminjaman, pengembalian, dan fitur denda, serta fitur booking online sebelum transaksi peminjaman, yang menjadi kebaruan dalam penelitian ini. Hasil pengujian Blackbox Pada fase pengujian akhir (iterasi 3) menunjukkan keseluruhan fungsionalitas aplikasi telah efektif dalam memenuhi tujuan fungsionalnya, dengan saran perbaikan pada peningkatan pengalaman pengguna dan efisiensi sistem.